1994
DOI: 10.1083/jcb.124.6.871
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular partitioning of MRP RNA assessed by ultrastructural and biochemical analysis

Abstract: Abstract. A small RNA encoded within the nucleus is an essential subunit of a RNA processing endonuclease (RNase MRP) hypothesized to generate primers for mitochondrial DNA replication from the heavy strand origin of replication. Controversy has arisen, however, concerning the authenticity of an intramitochondrial pool of MRP RNA, and has called into question the existence of pathways for nucleomitochondrial transport of nucleic acids in animal cells. In an effort to resolve this controversy, we combined ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 66 publications
4
85
1
1
Order By: Relevance
“…Furthermore, only one of three tRNA Gln isoforms is imported into Tetrahymena mitochondria (Rusconi and Cech, 1996), and only tRNA Lys , and no other tRNA, is imported into yeast mitochondria , most likely on the basis of sequence-specific determinants (Entelis et al, 1998). Similarly, deletion experiments imply that mouse MRP RNA also contains importation determinants (Li et al, 1994). Thus, it is reasonable to assume that a similar importation specificity applies to mammalian 5S rRNA.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, only one of three tRNA Gln isoforms is imported into Tetrahymena mitochondria (Rusconi and Cech, 1996), and only tRNA Lys , and no other tRNA, is imported into yeast mitochondria , most likely on the basis of sequence-specific determinants (Entelis et al, 1998). Similarly, deletion experiments imply that mouse MRP RNA also contains importation determinants (Li et al, 1994). Thus, it is reasonable to assume that a similar importation specificity applies to mammalian 5S rRNA.…”
Section: Discussionmentioning
confidence: 98%
“…are encoded by nuclear DNA (nDNA), synthesized in the cytosol, and imported into the organelle (Schatz and Dobberstein, 1996;Neupert, 1997). The same is true for all enzymes involved in the myriad metabolic pathways that take place in the mitochondrial environment.Interestingly, at least two mitochondrial enzymes, RNase MRP (a site-specific endoribonuclease involved in primer RNA metabolism in mammalian mitochondria [Chang and Clayton, 1987;Topper and Clayton, 1990;Li et al, 1994]) and RNase P (an endoribonuclease involved in tRNA processing [Doerson et al, 1985]), are ribonucleoproteins that contain an RNA moiety that is encoded by nDNA and is imported into the organelle. However, unlike the mechanisms for protein import into mitochondria, the mechanisms of RNA import into mitochondria are poorly understood.…”
mentioning
confidence: 99%
“…RNase MRP (mitochondrial RNA processing) was first identified as a ribonucleoprotein enzyme capable of in vitro formation of primers for mitochondrial DNA replication (Chang & Clayton, 1987;Schmitt & Clayton, 1992;)+ However, most of the enzyme is localized to the nucleolus (Reddy et al+, 1981;Reimer et al+, 1988;Kiss & Filipowicz, 1992), with only minute amounts found in the mitochondria (Topper et al+, 1992;Li et al+, 1994)+ Its cellular location suggested that the primary function of RNase MRP is in ribosome biogenesis+ Indeed, recent genetic evidence has established that RNase MRP is required for normal processing of 5+8S rRNA in Saccharomyces cerevisiae (Schmitt & Clayton, 1993b;Chu et al+, 1994;Lygerou et al+, 1994Lygerou et al+, , 1996+ The 5+8S rRNA of S. cerevisiae exists in short (5+8S S ) and long (5+8S L ) versions, differing by 6-7 nt at their 59 ends (Rubin, 1974;Lindahl et al+, 1992)+ The ratio of 5+8S S :5+8S L in wild-type cells is 5-10:1+ However, a single base change in the RNA subunit of RNase MRP results in a substantially decreased ratio of 5+8S S to 5+8S L , as well as accumulation of a very long version of 5+8S rRNA with 149 bases of the ITS1 sequence attached at the 59 end (Shuai & Warner, 1991;Lindahl et al+, 1992;Chu et al+, 1994)+ These observations together with other experiments (Henry et al+, 1994) have led to the conclusion that RNase MRP is responsible for initiating the processing of the short form of 5+8S rRNA by cleaving the pre-rRNA in the transcribed spacer between the 18S and 5+8S moieties+ RNase MRP is structurally related to RNase P, the endonucleolytic enzyme that creates the mature 59 end of tRNAs+ Both enzymes have one RNA subunit (here called MRP RNA and P RNA) that share secondarystructure features (Forster & Altman, 1990;Schmitt & Clayton, 1993a)+ Furthermore, RNases MRP and P of S. cerevisiae contain eight common protein subunits (Lygerou et al+, 1994;Chu et al+, 1997;Dichtl & Tollervey, 1997;Stolc & Altman, 1997;Chamberlain et al+, 1998;Stolc et al+, 1998); only one protein specific to each of the two nucleases has been identified (Schmitt & Clayton, 1994;…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Schon and colleagues have recently reported that a 5S ribosomal RNA may be imported, but its function has yet to be determined. 27 It is therefore possible that mammalian mitochondria do not possess an efficient import mechanism for nucleic acids.…”
Section: Mitochondrial Targeting and Importmentioning
confidence: 99%